Akuisisi Data Sederhana untuk Radar FM-CW - Adhi Purwoko (Pusat Penelitian Informatika - LIPI, 2011)
This paper describes the development of a simple data acquisition modul for FM-CW radar. The modul is design to be integrated in a through wall radar system using UWB and FM-CW technologies for life detector application. It uses a CY7C68013A, an EZ-USB family IC, from Cypress Semiconductor which is operated in slave FIFO mode. A Max II CPLD IC EPM1270T144 from Altera is used as a FIFO master. While for ADC, an AD9235 from Analog Devices is used. The modul is used to convert analog beat signal into digital data at a sampling rate of 1Msample/s and a resolution of 12 bit per sample.